Extraintestinal Escherichia coli from camel carcasses: Phylogroups, serotypes, and markers of virulence - Matěj Hrala; Marina Joseph; Martina Florianová; Helena Juřicová; Ulrich Wernery; David Šmajs; Juraj Bosák (PLoS ONE, 2025)
Pathogenic Escherichia coli causes infections responsible for economic losses in animal herds worldwide. Although this bacterium is well studied in livestock and poultry, studies of camelid infections caused by extraintestinal pathogenic E. coli (ExPEC) are limited. In this study, a set of ExPEC from camel carcasses (n = 150) was characterized with respect to phylogenetic groups, 162 O serotypes, and 35 virulence-associated genes (VAGs) using PCR screening. ExPEC frequently belonged to phylogroup B1 (58.7%), followed by phylogroups C, A, and B2 (12.7%, 12.0%, and 9.3%, respectively). Additionally, the set of ExPEC contained 36 different serotypes. The ExPEC isolates were found to typically encode ≥5 tested VAGs, particularly those related to adhesion (afaI, fimA, pap, sfa, tsh), iron acquisition (fyuA, iroN, iucC, sitA), host cell damage (α-hly, cdt, cnf1, sat), invasion (ibeA), and bacterial protection (iss, ompT, traT). Moreover, ExPEC from camel adults and calves were different from each other. Among isolates from calves, prevalence was significantly higher for phylogroups C (q < 0.001) and E (q < 0.01), and ten VAGs, including fitness factors (eitA, fepC, fyuA, iroN, iss, iucD, ompT, sitA), as well as VAGs with stronger link to pathogenicity (hlyF, and pap). To identify potential reservoir of camel ExPEC strains, fecal E. coli (n = 139) from healthy camels were also analyzed. Based on the identified characteristics, ExPEC were distinguishable from fecal isolates of healthy camels, suggesting an exogenous source of ExPEC infections, likely transmitted from wild birds and human keepers.